1, 2-Halosilane vs. 1, 2-alkylborane elimination from (boryl)(silyl) complexes of iron: switching between borylenes and silylenes just by changing the alkyl group. Issue 84 (8th September 2015) - Braunschweig, Holger; Dewhurst, Rian D.; Radacki, Krzysztof; Wennemann, Benedikt; Ye, Qing
Abstract : The results present a new elimination reaction, the 1, 2-alkylborane elimination, as a new route to silylene complexes. Abstract : Reaction of different combinations of aryl(dihalo)boranes and trialkylsilyl iron metallates, a route previously used to prepare a terminal iron arylborylene complex, is found to lead to three distinct new reaction outcomes, including unselective decomposition, an inert iron(ii ) (boryl)(silyl) complex, and a dinuclear bis(μ-silylene) complex. The latter result is to our knowledge the first example of a 1, 2-alkylborane elimination, in contrast to the facile and ubiquitous 1, 1-alkylborane elimination observed from (alkyl)(boryl) transition metal complexes, and is also a novel route to bridging silylene complexes.